(untitled) - Gnap, Jozef; Poliak, Milos (Doprava a spoje, 2007)
The article deals with the capacity analysis of road transport operators in suburban bus transport in Kosice region. The age and type structure of suburban transport buses is the result of analysis. The capacity of present transport operators is sufficient for fulfilment of contracts about the public interest performance in suburban bus transport